Introduction to Probability : With Mathematicaâ - Kao, Edward P C (London : World Scientific, 2022)
The main objective of this text is to facilitate a student's smooth learning transition from a course on probability to its applications in various areas. To achieve this goal, students are encouraged to experiment numerically with problems requiring computer solutions.
Includes index.
Keywords: Probability; Random variables; Limit theorems; Joint distribution